Resurrection of Amolops nepalicus Yang, 1991 (Amphibia: Anura: Ranidae), with Comments on the Record of A. cf. afghanus in Nepal and China and the Validity of Two Other Junior Synonyms of A. marmoratus (Blyth, 1855) - Wang, Kai; Bhattarai, Santosh; Wu, Yunhe; Che, Jing; Siler, Cameron D. (Zootaxa, 2020)
The taxonomic validity of the controversial taxon, Amolops nepalicus Yang, 1991, is evaluated based on the examination of its holotype, along with topotypic A. marmoratus (Blyth, 1855) and A. afghanus (Günther, 1858), and other related congeners. Morphological comparison shows the holotype of A. nepalicus differs from its senior synonym A. marmoratus and all recognized species, supporting its valid species status. We provide a detailed redescription of the holotype based on a robust morphometric dataset and expanded comparisons with recognized congeners from the Pan-Himalayas and Southeast Asia. In addition, we discuss the remaining suspicious records of A. cf. afghanus in Nepal and China based on available specimens, and comment on the validity of two remaining junior synonyms of A. marmoratus, namely Ixalus argus Annandale, 1912 and Rana latopalmata Boulenger, 1882, suggesting that they may represent subjective synonyms of A. gerbillus (Annandale, 1912) and A. panhai Matsui and Nabhitabhata, 2006, respectively.